If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 36 + 6c = 60 Solving 36 + 6c = 60 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + 6c = 60 + -36 Combine like terms: 36 + -36 = 0 0 + 6c = 60 + -36 6c = 60 + -36 Combine like terms: 60 + -36 = 24 6c = 24 Divide each side by '6'. c = 4 Simplifying c = 4
| 2/3(x-5)+1/2x+3 | | 4s+13=29 | | 8-4i/14i | | -6=x/12 | | -3x+5=-19 | | 1-5i/5+i | | 2x-1=97 | | (3p-8)/12=p/5 | | 3x+4=2x+2(x-7) | | (4x+1)(x-5)=0 | | (3p-8)/12=p/8 | | x^2(2x+3)=0 | | 0.5m+3=5 | | x(5x+3)=0 | | 3p-8/12=p/5 | | 5(3x+5)-12x=24 | | 14b^2-23b-15=0 | | 6x^2+7x=10 | | -4x+12.5=0.25x+4 | | 6x^2+x=10 | | 6x^2-29x-35=0 | | 4x-7=32x+14 | | 2x(x+3)(x-4)=0 | | y/9=6 | | 9x^2(x+4)=0 | | Y=3lnx | | .15X-3.2=1.3 | | -9+6=-18+3y | | 8a+5=5(3a-2)+1 | | 8/20-1/20 | | 5(x+6)-7=13 | | n-13=30 |